A novel lysophosphatidylcholine acyl transferase activity is expressed by peroxiredoxin 6 - Fisher, Aron B. (J Lipid Res, 2016)
The phospholipase A(2) (PLA(2)) activity of peroxiredoxin (Prdx)6 has important physiological roles in the synthesis of lung surfactant and in the repair of peroxidized cell membranes. These functions require the activity of a lysophospholipid acyl transferase as a critical component of the phospholipid remodeling pathway. We now describe a lysophosphatidylcholine acyl transferase (LPCAT) activity for Prdx6 that showed a strong preference for lysophosphatidylcholine (LPC) as the head group and for palmitoyl CoA in the acylation reaction. The calculated kinetic constants for acylation were K(m) 18 μM and V(max) 30 nmol/min/mg protein; the V(max) was increased 25-fold by phosphorylation of the protein while K(m) was unchanged. Study of recombinant protein in vitro and in mouse pulmonary microvascular endothelial cells infected with a lentiviral vector construct indicated that amino acid D31 is crucial for LPCAT activity. A linear incorporation of labeled fatty acyl CoA into dipalmitoyl phosphatidylcholine (PC) indicated that LPC generated by Prdx6 PLA(2) activity remained bound to the enzyme for the reacylation reaction. Prdx6 is the first LPCAT enzyme with demonstrated cytoplasmic localization. Thus, Prdx6 is a complete enzyme comprising both PLA(2) and LPCAT activities for the remodeling pathway of PC synthesis or for repair of membrane lipid peroxidation.